Attitudes Toward Guns Scale (ATGS):: Evidence of its Psychometric Adequacy - Nascimento, Thiago Gomes (2016)
This study aimed to verify the construct validity of the Attitude Towards Guns Scale (ATGS). The sample instudy 1 was composed by 200 policemen, with a mean age of 27.75 years (SD=2.98), 88.8% being men. They responded tothe ATGS questionnaire and to demographic questions. A principal components analysis indicated a three-factor structure,with Cronbach’s alphas of .81 (justice), .76 (protection) and .65 (crimes). The sample in Study 2 was composed by 220college students, with a mean age of 24.37 years (SD=7.58), 53% being females. The three-factor structure was tested usingconfirmatory factor analysis. The fit indexes were satisfactory. Cronbach’s Alphas of the Study 2 were .81, .76 and .75. Thestudy indicates that women tend to associate guns with crime while men tend to associate them with protection and justice.